2006
DOI: 10.1021/ie060695y
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of a Water Drop Triggered by the Surface Tension Gradient Created by the Localized Addition of a Surfactant

Abstract: The spreading of aqueous solutions of trisiloxane surfactants on solid surfaces has been studied extensively. Trisiloxane surfactants are used in pesticide delivery as adjuvants to promote spreading on leaves and provide a larger area for solute transfer. The spreading of a dew-drop on a leaf when a spray of pesticide is delivered is simulated by studying the spreading of a water drop on a hydrophobic surface when a small drop of aqueous trisiloxane surfactant is brought in contact with it. This study reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…In the previous studies, it was shown that the superspreading behavior of surfactant solutions on a hydrophobic solid surface like polystyrene surface was driven by surface tension gradient at the expanding air-liquid interface [6,9,25,26]. At very low concentrations, increasing the surfactant concentration will lead to a larger decrease in surface tension and a larger surface tension gradient.…”
Section: Effect Of Surfactant Concentration On Spreading Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies, it was shown that the superspreading behavior of surfactant solutions on a hydrophobic solid surface like polystyrene surface was driven by surface tension gradient at the expanding air-liquid interface [6,9,25,26]. At very low concentrations, increasing the surfactant concentration will lead to a larger decrease in surface tension and a larger surface tension gradient.…”
Section: Effect Of Surfactant Concentration On Spreading Velocitymentioning
confidence: 99%
“…For example, the wetting behaviors of surfactants were studied on superhydrophobic surfaces prepared from alkylketene dimer (AKD) [8]. To simulate a spray of pesticide caused a dew drop to spread on a leaf surface, Chengara et al [9] studied the spreading of water drop on a hydrophobic surface when a small drop of trisiloxane surfactant was brought in contact with it. We recently reported a group of siloxane surfactants [10] and investigated their spreading behaviors on fresh wheat and cabbage surfaces [11].…”
Section: Introductionmentioning
confidence: 99%
“…Even with a low concentration (0.1 wt%), the surface tension of aqueous trisiloxane solutions is significantly lower (~22 mN/m) than that of pure water (~72 mN/m) and therefore the wetting ability of such solutions is dramatically improved [28]. A number of studies have been performed to investigate spontaneous wetting of hydrophobic surfaces by aqueous trisiloxane solutions [28][29][30][31]. During the drop impact process, surfactants could prevent the drop from recoiling and bouncing, thus enhancing the deposition efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This prevention of superspreading can be achieved by using surfactant concentrations that are too low (i.e., below the so-called cwc, or critical wetting concentration; Chengara et al, 2007) and/or a substrate that is too hydrophobic (e.g., perfluoroalkane; . There are several reasons why one should have serious doubts about the relevance of some recent papers when it comes to providing new insights into the superspreading phenomenon.…”
Section: Definition Of Superspreading-trisiloxane Surfactantsmentioning
confidence: 99%